The directions of protection and development of natural environment of a metropolis on the example of the Poznań Metropolitan Area = Kierunki ochrony i rozwoju środowiska przyrodniczego metropolii na przykładzie Poznańskiego Obszaru Metropolitalnego - Borucińska-Bieńkowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study is a presentation of issues related to directions of changes which take place in natural environment in heavily urbanized areas, in a metropolis and the interaction of the central city and municipalities of the metropolitan area in the issue of natural environment. It shows natural environment as an important factor influencing functional and spatial conditionings of a metropolitan area.
Keywords: natural environment; obszar metropolitalny; poznański obszar metropolitalny; metropolia; metropolitan area; metropolis